2016
DOI: 10.1111/jopr.12462
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Fracture and Wear Resistance of Dentures/Overdentures Utilizing Digital Technology: A Case Series Report

Abstract: Since it was first introduced into the dental world, computer-aided design/computer-aided manufacturing (CAD/CAM) technology has improved dramatically in regards to both data acquisition and fabrication abilities. CAD/CAM is capable of providing well-fitting intra- and extraoral prostheses when sound guidelines are followed. As CAD/CAM technology encompasses both surgical and prosthetic dental applications as well as fixed and removable aspects, it could improve the average quality of dental prostheses compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…It can be a potential material for application as a restorative material in fixed prosthodontics [34] , [38] . Computer-aided design (CAD) and computer-aided manufacturing (CAM) technologies have increased accuracy and made it easier for the fabrication of modern restorative and prosthetic materials [39] , [40] , [41] . Individual ceramic produced from CAD/CAM can be incorporated in the complete denture to increase their wear resistance [40] , [41] , [42] .…”
Section: Properties Of Pekkmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be a potential material for application as a restorative material in fixed prosthodontics [34] , [38] . Computer-aided design (CAD) and computer-aided manufacturing (CAM) technologies have increased accuracy and made it easier for the fabrication of modern restorative and prosthetic materials [39] , [40] , [41] . Individual ceramic produced from CAD/CAM can be incorporated in the complete denture to increase their wear resistance [40] , [41] , [42] .…”
Section: Properties Of Pekkmentioning
confidence: 99%
“…Computer-aided design (CAD) and computer-aided manufacturing (CAM) technologies have increased accuracy and made it easier for the fabrication of modern restorative and prosthetic materials [39] , [40] , [41] . Individual ceramic produced from CAD/CAM can be incorporated in the complete denture to increase their wear resistance [40] , [41] , [42] . Recently, CAD/CAM technologies are used in the fabrication of PEKK prosthetic restorations [39] , [43] , [44] .…”
Section: Properties Of Pekkmentioning
confidence: 99%
“…A cobalt‐chromium (Co‐Cr) framework immersed at the denture base has been used in overdentures supported by two implants in order to prevent its fracture . Regarding single implant‐retained mandibular overdentures, studies have suggested the inclusion of a metallic framework reinforcement such as a strengthened instrument inside the denture base.…”
mentioning
confidence: 99%
“…A cobalt-chromium (Co-Cr) framework immersed at the denture base has been used in overdentures supported by two implants in order to prevent its fracture. 12,13 Regarding single implant-retained mandibular overdentures, studies 5,14 have suggested the inclusion of a metallic framework reinforcement such as a strengthened instrument inside the denture base. A clinical report by Grageda and Rieck 15 described an edentulous patient with no complications after 2 years of using a conventional maxillary complete denture and single implant-retained mandibular overdenture reinforced by a metal framework.…”
mentioning
confidence: 99%
“…In the near future, CAD/CAM may well become the preferred fabrication method for most dental prostheses. 13 There is no definte study shows difference in mechanical and physical properties of either milled or pressed frameworks. In this study it was clear that CAD/CAM method of fabrication is better was than pressedthis study, it was concluded that PEEK based restorations shows better surface properties than those of PMMA based materials so it can be used for long term restorations.…”
Section: Discussionmentioning
confidence: 99%